RELIGIOUS ORIENTATION AS THE HIDDEN CURRICULUM IN THE LEARNING PROCESS DURING THE COVID-19 PANDEMIC - Mirza Basyiruddin; Rukayah; Roemintoyo (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Religious orientation is a hidden curriculum that affects the process of implementing education in an institution. This is evident from the existence of various religious activities held at schools to instill students’ religious values in order to make them religious individuals. This study aimed to reveal various religious activities occurred as a hidden curriculum in one of the public elementary schools in Kecamatan Kalijambe, Kabupaten Sragen. Two problems were investigated in this study. The first was to reveal various religious activities and their suitability with the religion professed by students. The second was to describe the process of these activities before and during the Covid-19 pandemic. This study utilized a qualitative approach because of the suitability of its characteristics to assess and describe the reality that occurred. Case study was a form of qualitative research chosen in this study since there were specific problems being studied. The results showed that there were religious activities such as praying before and after lessons, reciting Al-Quran, reading Asmaul Husna, scheduling dhuha prayers, dhuhur prayers in congregation, kultum after dhuhur prayer, routine infaq, saying greetings, and wearing neat uniforms. These activities had undergone implementation adjustments during the Covid-19 pandemic.